Hydrological Drought and Trend Analysis in Kızılırmak, Yeşilırmak and Sakarya Basins - Kartal, Veysi; Emiroglu, Muhammet Emin (Springer Basel Ag, 2024)
Water is one of the most essential elements for human life and must be provided for life necessities. Historical changes in hydro-meteorological data are vital for operating and planning water structures. Drought indices are commonly used in the literature to assess the drought. Long-term streamflow records were used to evaluate the hydrological drought based on the Stream Flow Drought Index (SDI) in Sakarya, K & imath;z & imath;l & imath;rmak and Ye & scedil;il & imath;rmak basins located in Turkey for 56 years (1965-2020) with sixteen stations. SDI values were calculated at 1-, 3-, 6-, and 12-month scales based on moving averages (MA) to analyze the drought. Run Test and Double Mass Curve were applied to analyze the streamflow data. Moreover, Sen's Innovative Trend Detection Test (SITDT), Innovative Polygon Trend Analysis (IPTA), Mann-Kendall and Sen's slope were applied to evaluate the trend in the streamflow. Findings show that similar results were obtained for SDI-1, SDI-3, SDI-6, and SDI-12 results based on MA at the same stations. Although different droughts occurred, normal droughts were observed more. Downward trends were detected in streamflow data based on IPTA, SITDT, Mann-Kendall and Sen's slope. As a result, assessment of hydrological drought and trend analysis in these basins will contribute to water resources planning and management in the basins.
Keywords: Hydrological drought; Trend analysis; Moving average; Streamflow